Quantitative Analysis of the Side Branch Orifice after Bifurcation Stenting Using En Face Processing of OCT Images: A Comparison between Xience V and Resolute Integrity Stent - Minami, Yoshiyasu (Coron Artery Dis, 2016)
OBJECTIVE: Methods for intravascular assessment of the side branch (SB) orifice after stenting are not readily available. The aim of this study is to assess the utility of an en face projection processing for optical coherence tomography (OCT) images for the SB evaluation. METHODS: Measurements of the SB orifice using en face OCT images were validated using a phantom model. Linear regression modeling was applied to estimated area measurements made on the en face images. The SB orifice was then analyzed in 88 patients with bifurcation lesions treated with either a Xience V (EES) or a Resolute Integrity (ZES). The SB orifice area (A) and the area obstructed by struts (B) were calculated, and the %open area was evaluated as (A-B)/A*100. RESULTS: Linear regression modeling demonstrated observed departures of the intercept and slope was not significantly different from 0 (−0.12 ± 0.22, p=0.59) and from 1 (1.01 ± 0.06, R(2)=0.88, p=0.87), respectively. In cases without SB dilatation, the %open area was significantly larger in EES group (n=25) than in ZES group (n=32) (89.2% [83.7–91.3] vs. 84.3% [78.9–87.8], P=0.04). A significant difference in the %open area between with and without SB dilatation was demonstrated in the ZES group (91.4% [86.1–94.0] vs. 84.3% [78.9–87.8], P=0.04). CONCLUSIONS: The accuracy of SB orifice measurement on the en face OCT image was validated using a phantom model. This novel approach can quantitatively evaluate the differences in SB orifice area free from struts among different stent types and different treatment strategies in vivo.